2020
DOI: 10.1080/03079457.2020.1753654
|View full text |Cite
|
Sign up to set email alerts
|

Active virological surveillance in backyard ducks in Bangladesh: detection of avian influenza and gammacoronaviruses

Abstract: Domestic waterfowl play an important role in the perpetuation and transmission of avian pathogens including avian influenza viruses (AIV) of low and high pathogenicity, which pose severe economic and public health concerns in Bangladesh. This study focused on active surveillance of several avian viral pathogens with a special reference to AIV in selected backyard duck populations in Bangladesh. A total of 500 pooled oropharyngeal and cloacal samples from individual ducks of four districts were tested by real t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Single-step RT-qPCR assays were performed with previously designed unique oligonucleotide primers for the detection of the untranslated regions (5′-UTR) and a fragment of the polymerase gene of avian gammacoronaviruses (AvCoV) in a single assay [ 13 ]. The assay was carried out using a Luna Universal One-Step RT-qPCR Kit (New England Biolabs Inc., USA) containing SYBR Green reagents following a slightly modified previous protocol [ 28 ]. The final reaction volume was 12.5 μL, including 2.5 μL of RNA template, 5 μL of 2x RT-PCR SYBR reaction mix, 0.5 μL of Luna WarmStart RT Enzyme Mix, 2.5 μL of nuclease-free water, and 2 μL of IBV primer mix (10 pmol each).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-step RT-qPCR assays were performed with previously designed unique oligonucleotide primers for the detection of the untranslated regions (5′-UTR) and a fragment of the polymerase gene of avian gammacoronaviruses (AvCoV) in a single assay [ 13 ]. The assay was carried out using a Luna Universal One-Step RT-qPCR Kit (New England Biolabs Inc., USA) containing SYBR Green reagents following a slightly modified previous protocol [ 28 ]. The final reaction volume was 12.5 μL, including 2.5 μL of RNA template, 5 μL of 2x RT-PCR SYBR reaction mix, 0.5 μL of Luna WarmStart RT Enzyme Mix, 2.5 μL of nuclease-free water, and 2 μL of IBV primer mix (10 pmol each).…”
Section: Methodsmentioning
confidence: 99%
“…Positive samples were further screened for IBV using probe-based (TaqMan) single-step RT-qPCR assays, using a Luna Universal Probe One-Step RT-qPCR Kit (New England Biolabs Inc., USA) and IBV-specific oligonucleotides [ 8 ]. All samples were screened for other respiratory viral pathogens, including avian influenza virus (AIV) and Newcastle disease virus (NDV) following a previously described protocol [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the endemic LPAI H9N2 viruses, other LPAI virus subtypes identified in domestic birds from LBM samples in Bangladesh include H4N6 and H11N3. Subtypes H1N1, H1N3, H1N5, H2N4, H2N5, H3N1, H3N2, H4N2, H5N2, H6N1, H7N1, H7N5, and H7N9 ( Supplemental Table S1 ) have been detected sporadically and mostly in domestic birds, especially backyard ducks or ducks sold in LBMs, but seldom in wild birds [ 22 , 29 , 36 ].…”
Section: Overview Of Aiv Sub- and Pathotypes In Bangladeshmentioning
confidence: 99%
“…Both viruses cause significant economic damage in poultry production and threaten public health by their zoonotic propensity [ 27 ]. AIV surveillance studies in Bangladesh [ 22 , 26 , 28 , 29 ] have shown that domestic ducks play an important role in the transmission and emergence of new AIV sub- and genotypes.…”
Section: Introductionmentioning
confidence: 99%